Identifying and predicting distinct distress trajectories following a breast cancer diagnosis - from treatment into early survival - Kant, Janina; Czisch, Agnieszka; Schott, Sarah; Siewerdt-Werner, Daniela; Birkenfeld, Frauke; Keller, Monika (Journal of psychosomatic research, 2018)
Objective - Most longitudinal studies on distress in breast cancer (BC) patients reported a continuous decrease after diagnosis, however masking individual variations in patterns of adjustment. We sought to identify distinct trajectories of distress during primary treatment into survivorship and to identify variables that are determinants of which patient follows which type of adjustment trajectory. - Methods - Psychological distress was measured at four significant time points (after surgery/biopsy, at treatment completion, two and six months thereafter) among 181 newly diagnosed BC patients. A latent growth mixture modeling approach was used to identify distinct distress trajectories. - Results - Four distress trajectories were identified: a ‘resilient’ pattern (73.1%), a ‘high-remitting’ (7.7%) trajectory, a ‘delayed’ increase in distress (7.9%), and a constantly high ‘chronic’ distress (11.3%) pattern. High perceived burden from physical symptoms at treatment completion encompassed a higher chance for the ‘high-remitting’ and ‘chronic’ distress trajectory. High self-efficacy at baseline increased chances for the ‘high-remitting’ pattern. Neither type of treatment, demographic or medical characteristics, nor baseline distress reliably predicted distress trajectories. - Conclusion - The majority of BC patients adjust well through a demanding treatment period. High patient-perceived burden from physical symptoms, and high coping self-efficacy is suggesting a transient, self-limiting distress trajectory, while patients experiencing constant ‘chronic’ distress, and those developing distress following treatment completion only cannot be identified by a single, initial assessment. Only systematic tracking with repeated measurement extending into survivorship can eliminate this problem. Interventions should aim at reducing the impact of symptom burden on women's every-day life and on strengthening coping-self efficacy.
Gesehen am 04.11.2019